Flexographic metal ink and printing process thereof

By developing flexographic metal inks containing unsaturated resins and reactive monomers, and using UV curing and release film flattening technology, the problems of poor environmental pollution and dispersion stability of existing metal inks have been solved, and high gloss and resistance are achieved The printing process with aging performance meets the market's demand for environmental protection and exquisiteness.

CN118834559BActive Publication Date: 2025-01-07GUANGZHOU MEIKEI INTELLIGENT PRINTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410876722.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2025-01-07
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

Most of the existing metal inks are solvent-based, with environmental pollution problems and lack of effective flexographic printing technology. The dispersion stability of water-based metal inks is poor, which cannot meet the market's demand for exquisiteness and environmental protection.

Method used

Develop a flexographic metal ink containing 32% to 36% unsaturated resin, 21% to 25% active monomer and 36% to 40% aluminum silver paste. The ink layer was formed through UV curing process, using a 300L net The anilox roller is used for ink transfer printing, and after printing, the release film is covered for flattening and light curing to achieve mirror flatness.

Benefits of technology

The preparation of solvation-free metal ink is achieved, which improves the gloss, adhesion and aging resistance of the ink layer, reduces environmental pollution, and provides a green and environmentally friendly printing process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of gravure metal ink, specifically to a flexographic metal ink and its printing process. A flexographic metal ink comprises the following mass components: 32% to 36% of a main resin, 21% to 25% of an active monomer, 36% to 40% of an aluminum-silver paste and 4% to 6% of an initiator. The present invention uses liquid resin, active monomer, photoinitiator and aluminum-silver paste as components to prepare a metal ink; the main resin contains unsaturated groups such as carbon-carbon double bonds and epoxy groups, which can undergo a curing reaction under the action of a photoinitiator during UV curing, so that the printed layer is cured into a film to form an ink layer; the active monomer can dissolve the prepolymer and adjust the viscosity, and can also participate in UV curing to improve the comprehensive performance of the ink layer, thereby realizing the solvent-free metal ink, which is more green and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gravure metal ink, in particular to a flexographic metal ink and a printing process thereof. Background Art

[0002] Gravure ink is a stable colored dispersion system that can be coated on the surface of the substrate in an appropriate printing method to present text patterns and colors, provide information and appeal. Gravure ink is mainly composed of pigments, resins, solvents, fillers and additives. With the improvement of economic level, people have a higher pursuit of exquisite things. Aluminum silver paste has a special glittering effect and is respected by more and more people. At present, most of the metallic inks on the market are solvent-based inks, which are prone to cause large pollution, affect the environment and personal safety, and there is currently no mature flexographic process that can replace them. Water-based metallic inks are less used and have poor dispersion stability. Therefore, we propose a flexographic metallic ink and its printing process. Summary of the invention

[0003] The object of the present invention is to provide a flexographic metal ink and a printing process thereof to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a flexographic metal ink, comprising the following mass components: 32% to 36% main resin, 21% to 25% active monomer, 36% to 40% aluminum silver paste and 4% to 6% initiator.

[0005] Furthermore, the main resin is an unsaturated resin containing unsaturated groups.

[0006] Furthermore, the main resin is a mixture of one or more of acrylic resin, epoxy resin, polyurethane resin, polyester resin and chloroacetic acid resin.

[0007] Furthermore, the active monomer is an acrylate monomer.

[0008] Furthermore, the initiator is a mixture of one or more of the photoinitiators Irgacure-907, Irgacure-184, Irgacure-127, Irgacure-1173, Irgacure-2959, Irgacure-MBF, Irgacure-754, and Irgacure-784.

[0009] In the above technical solution, the main resin is the main film-forming part of the metallic ink, which determines the adhesion, water resistance, flexibility and corrosion resistance of the metallic ink cured film. The main resin contains unsaturated groups such as carbon-carbon double bonds and epoxy groups, which can be cured by photoinitiators during UV curing to cure the printed layer into a film and form an ink layer. The active monomer can dissolve the prepolymer and adjust the viscosity, and can also participate in UV curing to improve the overall performance of the ink layer.

[0010] A printing process of flexographic metal ink includes the following process steps: taking metal ink for ink transfer printing; then covering the surface of the metal ink with a release film, flattening it, UV curing it, and forming an ink layer; finally peeling the release film from the ink layer.

[0011] Furthermore, the ink transfer printing is carried out using a 300L anilox roller with a printing speed of 75-85 m / min. 300L can reasonably simulate the ink layer thickness of gravure printing.

[0012] Furthermore, flattening is the physical squeezing of undried metallic ink by a pressure roller, which can make the metallic ink layer obtained after ink transfer printing quickly reach a mirror-like flatness effect and increase the glossiness of the metallic ink layer.

[0013] Furthermore, in the UV curing process, the UV lamp is 7000-12000W, the irradiation speed is 75-85m / min, and the irradiation distance is 5-8cm.

[0014] The UV curing process is carried out in the extruded state of the metallic ink layer. Both the metallic ink layer and the release film are placed under a UV lamp for irradiation. The cured surface of the metallic ink layer is the same as the surface of the release film, and the same mirror flatness as the release film is obtained.

[0015] The release film should be smooth and non-adhesive. The ink layer and the release film are peeled off and separated by an independent retracting unit, and then presented by subsequent processes to achieve the diversification of metallic ink printing products.

[0016] Furthermore, the metal ink is prepared by the following process: under light-proof conditions, the main resin, active monomer and initiator are mixed, aluminum silver paste is added, pre-mixed by a gravity mixer, and ground by a grinder to a fineness of less than 5 μm.

[0017] Further, the main resin is prepared by the following process:

[0018] The polyhydroxy rosin compound, diacid and catalyst are mixed, heated to 150-160° C. under nitrogen atmosphere protection, and reacted for 100-150 minutes; diol, unsaturated acid and inhibitor are added, the temperature is raised to 210-220° C., reacted until the system state is transparent, the vacuum degree is reduced, the negative pressure is stabilized at 0.05-0.07 MPa, vacuumed for 60 minutes, reacted until the acid value is less than 5 mgKOH / g, cooled to room temperature, and the main resin is obtained.

[0019] Further, the diacid is one of phthalic anhydride and 1,6-adipic acid;

[0020] The diol is a mixture of one or more of 1,6-hexanediol, neopentyl glycol, and 2-butyl-2-ethyl-1,3-propanediol;

[0021] The unsaturated acid is one of acrylic acid, methacrylic acid, itaconic acid and maleic anhydride.

[0022] Furthermore, the main resin is prepared from the following components by mass: 22 to 27 parts of a polyhydroxy rosin compound, 18 to 22 parts of 2-butyl-2-ethyl-1,3-propanediol, 11 to 13 parts of neopentyl glycol, 14 to 20 parts of phthalic anhydride, 2 to 5 parts of itaconic acid, 0.1 to 1.0 parts of a catalyst dibutyltin oxide, and 0.1 to 1.0 parts of an inhibitor p-hydroxyanisole.

[0023] Further, the polyhydroxy rosin compound is prepared by the following process:

[0024] 1.1. Mix linoleic acid, pimaric acid and deionized water, add catalyst and activated clay, heat and melt under nitrogen atmosphere protection, raise the temperature to 230-250°C, control the pressure of the pressure reactor at 0.4-0.6MPa, and react for 4-6h; cool to 100°C, neutralize with phosphoric acid, react for 30min, cool to room temperature, filter, dissolve with dimethyl sulfoxide, wash, and distill under reduced pressure to obtain rosin diacid;

[0025] 1.2. Mix diglycidyl ether, rosin diacid and tetrabutylammonium bromide, raise the temperature to 130-140°C, keep the temperature to react until the acid value is less than 5mg / KOH, and cool to room temperature to obtain a dihydroxyrosin compound;

[0026] A potassium hydroxide aqueous solution is added, the temperature is raised to 80-90° C., and the mixture is reacted for 10-12 hours; the mixture is washed, dried, and distilled under reduced pressure to obtain a polyhydroxy rosin compound.

[0027] Further, in step 1.1, rosin diacid is prepared from the following components by mass: 2.0-2.2 parts of pimaric acid, 10 parts of linoleic acid, 0.10-0.15 parts of catalyst manganese acetate, and 1.0-1.5 parts of activated clay;

[0028] The ratio of linoleic acid to deionized water is 20 g / 100 mL.

[0029] Further, in step 1.2, the diglycidyl ether is one of 1,6-hexanediol diglycidyl ether and 1,2-cyclohexanediol diglycidyl ether;

[0030] The mass ratio of diglycidyl ether and rosin diacid is (1.2-1.4):1;

[0031] The tetrabutylammonium bromide is 0.8% to 1.5% of the total mass of diglycidyl ether and rosin diacid.

[0032] Furthermore, in step 1.2, the ratio of the dihydroxyrosin compound to the potassium hydroxide aqueous solution (20 wt%) is 10 g / 10 mL.

[0033] In the above technical scheme, linoleic acid is thermally isomerized to conjugated linoleic acid, which reacts with pimaric acid to form a dibasic acid with a non-cyclic structure. The addition of water to the reaction system facilitates the DA addition reaction and reduces the occurrence of side reactions. The introduction of heat-resistant fused rings in rosin can improve the mechanical properties and heat resistance of metallic ink, help improve the toughness, aging resistance and adhesion of the ink layer to the printed substrate; and can also give the ink layer a higher gloss. The rosin diacid prepared by the addition of linoleic acid and pimaric acid reacts with the epoxy group in diglycidyl ether to generate hydroxyl groups, and by controlling the amount of the substance, the prepared dihydroxy rosin compound contains two epoxy groups, which are opened to form a tetrahydroxy structure to obtain a polyhydroxy rosin compound. As a hydroxyl component, it participates in the esterification reaction between the components of the main resin, reacts with 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, phthalic anhydride, and itaconic acid to form a polyester resin with a branched structure, and its end group uses itaconic acid to introduce unsaturated carbon-carbon double bonds to achieve and participate in the subsequent process of light curing. The branched structure of the main resin can be cross-linked with the active monomer during the light curing stage to form a three-dimensional network structure, which increases the cross-linking density, promotes the densification of the ink layer, and helps to improve its gloss, mechanical properties and aging resistance.

[0034] Furthermore, the active monomer includes the following components by mass: 14 to 15 parts of methyl methacrylate, 23 to 25 parts of styrene, 11 to 13 parts of 2-hydroxyethyl methacrylate, 37 to 40 parts of butyl acrylate, 4 to 5 parts of n-butyl methacrylate, 3 to 15 parts of trimethylolpropane triacrylate, 1 to 8 parts of ester alcohol dodeca-methacrylate, and 3 to 5 parts of ethylene glycol methyl ether methacrylate.

[0035] Further, ester alcohol twelve-methylacrylate is prepared by the following process:

[0036] Mix ester alcohol dodeca-methylbenzene and toluene, heat to 105-110°C under nitrogen atmosphere, add metallic sodium, and react for 180-200 min; cool to room temperature, filter to remove the remaining metallic sodium; cool to 0-5°C, slowly add methacryloyl chloride, add it over 30 min, restore the temperature to 20-27°C, stir and react for 8-12 h; let stand, filter, rotary evaporate, dissolve, wash, rotary evaporate the organic phase, and dry to obtain ester alcohol dodeca-methylbenzene.

[0037] Further, the molar ratio of ester alcohol dodecahydrate and methacryloyl chloride is 1:(1.0-1.1);

[0038] The ratio of ester alcohol dodecahydrate, metallic sodium and toluene is 20g:(2-5)g:100mL.

[0039] Furthermore, the initiator is a compound of photoinitiators Irgacure-907 and Irgacure-1173, with a mass ratio of 1:1.

[0040] In the above technical solution, the active monomer is a compound of a plurality of unsaturated compounds containing alkenyl groups, which helps to improve the water resistance, heat resistance, color retention, flexibility, adhesion and other properties of the ink layer made of the metal ink. The active monomer also contains ester alcohol dodeca-methacrylate, and the ester alcohol dodeca structure is introduced by the reaction between ester alcohol dodeca and methacryloyl chloride, which cooperates with ethylene glycol methyl ether methacrylate to improve the dissolution of the active monomer in the main resin, promote the stability of the metal ink, and improve the printing film formation and toughness.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. The flexographic metal ink described in the present invention is prepared with liquid resin, active monomer, photoinitiator and aluminum silver paste as components; the main resin contains unsaturated groups such as carbon-carbon double bonds and epoxy groups, which can undergo a curing reaction under the action of the photoinitiator during UV curing, so that the printed layer is cured into a film to form an ink layer; the active monomer can dissolve the prepolymer and adjust the viscosity, and can also participate in UV curing to improve the comprehensive performance of the ink layer, thereby realizing solvent-free metal ink and being more environmentally friendly.

[0043] 2. The present invention describes a printing process for flexographic metallic ink, which covers the surface of the printed metallic ink layer with a release film, flattens it, and then performs photocuring, so that the cured surface of the metallic ink layer is the same as the surface of the release film, thereby obtaining the same mirror flatness as the release film. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] In the following specific implementations,

[0046] Activated clay: HT-1A comes from Anji Gaochao Activated Clay Co., Ltd.

[0047] Aluminum paste: L-3008, from Hefei Xuyang Aluminum Pigment Co., Ltd.

[0048] Release film: PET fluorine release film, from Tianjin Zhengzhong New Material Technology Co., Ltd.

[0049] Embodiment 1: A printing process of flexographic metal ink, comprising the following process steps:

[0050] Step 1, (1) 20g of linoleic acid, pimaric acid and 100mL of deionized water are mixed, a catalyst and activated clay are added, and the mixture is heated to melt under the protection of a nitrogen atmosphere, the temperature is raised to 230°C, the pressure of the pressure-resistant reactor is controlled at 0.6MPa, and the reaction is performed for 6h; the mixture is cooled to 100°C, neutralized with phosphoric acid, reacted for 30min, cooled to room temperature, filtered, dissolved and washed with dimethyl sulfoxide, and distilled under reduced pressure to obtain rosin diacid; the rosin diacid is prepared from the following components by mass: 2.0 parts of pimaric acid, 10 parts of linoleic acid, 0.10 parts of catalyst manganese acetate, and 1.0 parts of activated clay;

[0051] 1,6-hexanediol diglycidyl ether, rosin diacid, and 0.8% tetrabutylammonium bromide were mixed, heated to 130°C, kept warm for reaction until the acid value was <5mg / KOH, and cooled to room temperature to obtain a dihydroxy rosin compound; the mass ratio of 1,6-hexanediol diglycidyl ether to rosin diacid was 1.2:1; 20wt% potassium hydroxide aqueous solution was added, the temperature was raised to 80°C for reaction for 12h; washed, dried, and distilled under reduced pressure to obtain a polyhydroxy rosin compound; the ratio of the dihydroxy rosin compound to the potassium hydroxide aqueous solution (20wt%) was 10g / 10mL;

[0052] The polyhydroxy rosin compound, phthalic anhydride and a catalyst are mixed, heated to 150° C. under nitrogen atmosphere protection, and reacted for 150 minutes; 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, itaconic acid and a polymerization inhibitor are added, the temperature is raised to 210° C., reacted until the system state is transparent, the vacuum degree is reduced, the negative pressure is stabilized at 0.07 MPa, vacuumed for 60 minutes, reacted until the acid value is less than 5 mgKOH / g, and cooled to room temperature to obtain a main resin; the main resin is prepared from the following components by mass: 22 parts of polyhydroxy rosin compound, 18 parts of 2-butyl-2-ethyl-1,3-propanediol, 11 parts of neopentyl glycol, 14 parts of phthalic anhydride, 2 parts of itaconic acid, 0.5 parts of catalyst dibutyltin oxide, and 0.5 parts of polymerization inhibitor p-hydroxyanisole;

[0053] (2) Mix ester alcohol dodecahydrate and toluene, heat to 105°C under nitrogen atmosphere, add sodium metal, and react for 200 minutes; cool to room temperature, filter to remove the remaining sodium metal; cool to 5°C, slowly add methacryloyl chloride, add for 30 minutes, restore the temperature to 20°C, stir and react for 12 hours; let stand, filter, rotary evaporate, dissolve, wash, take the organic phase, rotary evaporate, and dry to obtain ester alcohol dodecahydrate-methacrylate; the molar ratio of ester alcohol dodecahydrate to methacryloyl chloride is 1:1; the ratio of ester alcohol dodecahydrate to sodium metal and toluene is 20g:2g:100mL;

[0054] (3) Under light-proof conditions, a main resin, an active monomer and an initiator are mixed, aluminum silver paste is added, and the mixture is pre-mixed using a gravity mixer, and the mixture is ground with a grinder to a fineness of less than 5 μm to obtain a metallic ink; the metallic ink comprises the following components by mass: 32% main resin, 25% active monomer, 38% aluminum silver paste and 5% initiator; the active monomer comprises the following components by mass: 15 parts of methyl methacrylate, 25 parts of styrene, 13 parts of 2-hydroxyethyl methacrylate, 40 parts of butyl acrylate, 5 parts of n-butyl methacrylate, 3 parts of trimethylolpropane triacrylate, 1 part of ester alcohol dodeca-methacrylate, and 3 parts of ethylene glycol methyl ether methacrylate; the initiator is a compound of photoinitiators Irgacure-907 and Irgacure-1173, and the mass ratio is 1:1;

[0055] Step 2: Take metallic ink and use a 300L anilox roller for ink transfer printing at a printing speed of 80m / min; then cover the surface of the metallic ink with a layer of release film, and use a pressure roller to physically extrude and flatten the undried metallic ink; UV curing, UV curing, UV curing irradiation speed of 80m / min, irradiation distance of 6cm, ultraviolet lamp 7000W, to form an ink layer; finally, peel off the release film and the ink layer.

[0056] Embodiment 2: A printing process of flexographic metal ink, comprising the following process steps:

[0057] Step 1, (1) 20g of linoleic acid, pimaric acid and 100mL of deionized water are mixed, a catalyst and activated clay are added, and the mixture is heated to melt under the protection of a nitrogen atmosphere, the temperature is raised to 240°C, the pressure of the pressure-resistant reactor is controlled at 0.5MPa, and the reaction is performed for 5h; the mixture is cooled to 100°C, neutralized with phosphoric acid, reacted for 30min, cooled to room temperature, filtered, dissolved and washed with dimethyl sulfoxide, and distilled under reduced pressure to obtain rosin diacid; the rosin diacid is prepared from the following components by mass: 2.1 parts of pimaric acid, 10 parts of linoleic acid, 0.12 parts of catalyst manganese acetate, and 1.2 parts of activated clay;

[0058] 1,2-cyclohexanediol diglycidyl ether, rosin diacid, and 1.2% tetrabutylammonium bromide were mixed, heated to 135°C, kept warm for reaction until the acid value was <5mg / KOH, and cooled to room temperature to obtain a dihydroxy rosin compound; the mass ratio of 1,2-cyclohexanediol diglycidyl ether to rosin diacid was 1.3:1;

[0059] Add 20 wt% potassium hydroxide aqueous solution, heat to 85°C and react for 11 hours; wash, dry, and distill under reduced pressure to obtain a polyhydroxy rosin compound; the ratio of the dihydroxy rosin compound to the potassium hydroxide aqueous solution (20 wt%) is 10 g / 10 mL;

[0060] The polyhydroxy rosin compound, phthalic anhydride and a catalyst are mixed, heated to 155° C. under nitrogen atmosphere protection, and reacted for 20 minutes; 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, itaconic acid and a polymerization inhibitor are added, the temperature is raised to 215° C., reacted until the system state is transparent, the vacuum degree is reduced, the negative pressure is stabilized at 0.06 MPa, vacuumed for 60 minutes, reacted until the acid value is less than 5 mgKOH / g, and cooled to room temperature to obtain a main resin; the main resin is prepared from the following components by mass: 25 parts of polyhydroxy rosin compound, 20 parts of 2-butyl-2-ethyl-1,3-propanediol, 12 parts of neopentyl glycol, 17 parts of phthalic anhydride, 3 parts of itaconic acid, 0.8 parts of catalyst dibutyltin oxide, and 0.8 parts of polymerization inhibitor p-hydroxyanisole;

[0061] (2) Mix ester alcohol dodecahydrate and toluene, heat to 108°C under nitrogen atmosphere, add sodium metal, and react for 190 minutes; cool to room temperature, filter to remove the remaining sodium metal; cool to 2°C, slowly add methacryloyl chloride, add for 30 minutes, restore the temperature to 25°C, stir and react for 10 hours; let stand, filter, rotary evaporate, dissolve, wash, take the organic phase, rotary evaporate, and dry to obtain ester alcohol dodecahydrate-methacrylate; the molar ratio of ester alcohol dodecahydrate to methacryloyl chloride is 1:1.05; the ratio of ester alcohol dodecahydrate to sodium metal and toluene is 20g:3g:100mL;

[0062] (3) Under light-proof conditions, the main resin, active monomer and initiator are mixed, aluminum silver paste is added, and the mixture is pre-mixed by a gravity mixer, and ground by a grinder to a fineness of less than 5 μm to obtain a metallic ink; the metallic ink comprises the following components by mass: 34% main resin, 23% active monomer, 38% aluminum silver paste and 5% initiator; the active monomer comprises the following components by mass: 14.5 parts of methyl methacrylate, 24 parts of styrene, 12 parts of 2-hydroxyethyl methacrylate, 38 parts of butyl acrylate, 4.5 parts of n-butyl methacrylate, 9 parts of trimethylolpropane triacrylate, 5 parts of ester alcohol dodeca-methacrylate, and 4 parts of ethylene glycol methyl ether methacrylate; the initiator is a compound of photoinitiators Irgacure-907 and Irgacure-1173, with a mass ratio of 1:1;

[0063] Step 2: Take metallic ink and use a 300L anilox roller for ink transfer printing at a printing speed of 80m / min; then cover the surface of the metallic ink with a layer of release film, and use a pressure roller to physically extrude and flatten the undried metallic ink; UV curing, UV curing, UV curing irradiation speed of 80m / min, irradiation distance of 6cm, ultraviolet lamp 7000W, to form an ink layer; finally, peel off the release film and the ink layer.

[0064] Embodiment 3: A printing process of flexographic metal ink, comprising the following process steps:

[0065] Step 1, (1) 20g of linoleic acid, pimaric acid and 100mL of deionized water are mixed, catalysts such as manganese acetate and activated clay are added, and the mixture is heated to melt under the protection of a nitrogen atmosphere, and the temperature is raised to 250°C, and the pressure of the pressure-resistant reactor is controlled at 0.4MPa, and the reaction is carried out for 4h; the mixture is cooled to 100°C, neutralized with phosphoric acid, reacted for 30min, cooled to room temperature, filtered, dissolved and washed with dimethyl sulfoxide, and distilled under reduced pressure to obtain rosin diacid; the rosin diacid is prepared from the following components by mass: 2.2 parts of pimaric acid, 10 parts of linoleic acid, 0.15 parts of catalyst, and 1.5 parts of activated clay;

[0066] 1,6-hexanediol diglycidyl ether, rosin diacid, and 1.5% tetrabutylammonium bromide were mixed, heated to 140°C, kept warm for reaction until the acid value was <5mg / KOH, and cooled to room temperature to obtain a dihydroxy rosin compound; the mass ratio of diglycidyl ether to rosin diacid was 1.4:1; 20wt% potassium hydroxide aqueous solution was added, the temperature was raised to 90°C for reaction for 10h; washed, dried, and distilled under reduced pressure to obtain a polyhydroxy rosin compound; the ratio of dihydroxy rosin compound to potassium hydroxide aqueous solution (20wt%) was 10g / 10mL;

[0067] The polyhydroxy rosin compound, phthalic anhydride and a catalyst are mixed, heated to 160° C. under nitrogen atmosphere protection, and reacted for 100 minutes; 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, itaconic acid and a polymerization inhibitor are added, the temperature is raised to 220° C., reacted until the system state is transparent, the vacuum degree is reduced, the negative pressure is stabilized at 0.05 MPa, vacuumed for 60 minutes, reacted until the acid value is less than 5 mgKOH / g, and cooled to room temperature to obtain a main resin; the main resin is prepared from the following components by mass: 27 parts of polyhydroxy rosin compound, 22 parts of 2-butyl-2-ethyl-1,3-propanediol, 13 parts of neopentyl glycol, 20 parts of phthalic anhydride, 5 parts of itaconic acid, 1.0 part of catalyst dibutyltin oxide, and 1.0 part of polymerization inhibitor p-hydroxyanisole;

[0068] (2) Mix ester alcohol dodecahydrate and toluene, heat to 110°C under nitrogen atmosphere, add sodium metal, and react for 180 minutes; cool to room temperature, filter to remove the remaining sodium metal; cool to 0°C, slowly add methacryloyl chloride, add for 30 minutes, restore the temperature to 27°C, stir and react for 8 hours; let stand, filter, rotary evaporate, dissolve, wash, take the organic phase, rotary evaporate, and dry to obtain ester alcohol dodecahydrate-methacrylate; the molar ratio of ester alcohol dodecahydrate to methacryloyl chloride is 1:1.1; the ratio of ester alcohol dodecahydrate to sodium metal and toluene is 20g:5g:100mL;

[0069] (3) In a light-proof condition, a main resin, an active monomer and an initiator are mixed, and aluminum-silver paste is added, and the mixture is pre-mixed by a gravity mixer, and then ground by a grinder to a fineness of less than 5 μm to obtain a metallic ink; the metallic ink comprises the following components by weight: 36% main resin, 21% active monomer, 38% aluminum-silver paste and 5% initiator;

[0070] The active monomers include the following components by weight: 14 parts of methyl methacrylate, 23 parts of styrene, 11 parts of 2-hydroxyethyl methacrylate, 37 parts of butyl acrylate, 4 parts of n-butyl methacrylate, 15 parts of trimethylolpropane triacrylate, 8 parts of ester alcohol dodeca-methacrylate, and 5 parts of ethylene glycol methyl ether methacrylate; the initiator is a compound of photoinitiators Irgacure-907 and Irgacure-1173, with a mass ratio of 1:1;

[0071] Step 2: Take metallic ink and use a 300L anilox roller for ink transfer printing at a printing speed of 80m / min; then cover the surface of the metallic ink with a layer of release film, and use a pressure roller to physically extrude and flatten the undried metallic ink; UV curing, UV curing, UV curing irradiation speed of 80m / min, irradiation distance of 6cm, ultraviolet lamp 7000W, to form an ink layer; finally, peel off the release film and the ink layer.

[0072] Comparative Example 1: A printing process of flexographic metallic ink:

[0073] The active monomers include the following components by mass: 15 parts of methyl methacrylate, 25 parts of styrene, 13 parts of 2-hydroxyethyl methacrylate, 40 parts of butyl acrylate, 5 parts of n-butyl methacrylate, and 3 parts of trimethylolpropane triacrylate;

[0074] The other processes and steps are the same as those in Example 1 to obtain metallic ink and printed products thereof.

[0075] Comparative Example 2: A printing process of flexographic metal ink, comprising the following process steps:

[0076] Step 1, mixing rosin diacid, phthalic anhydride and a catalyst, heating to 150° C. under nitrogen atmosphere protection, and reacting for 150 minutes; adding 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, itaconic acid and a polymerization inhibitor, heating to 210° C., reacting until the system state is transparent, reducing the vacuum degree, stabilizing the negative pressure at 0.07 MPa, evacuating for 60 minutes, reacting until the acid value is less than 5 mgKOH / g, cooling to room temperature, and obtaining a main resin; the main resin is prepared from the following mass components: 39 parts of rosin diacid, 18 parts of 2-butyl-2-ethyl-1,3-propanediol, 11 parts of neopentyl glycol, 14 parts of phthalic anhydride, 2 parts of itaconic acid, 0.5 parts of catalyst dibutyltin oxide, and 0.5 parts of polymerization inhibitor p-hydroxyanisole;

[0077] The other processes and steps are the same as those in Example 1 to obtain metallic ink and printed products thereof.

[0078] Comparative Example 3: A printing process of flexographic metal ink, comprising the following process steps:

[0079] Step 1, trimethylolpropane, phthalic anhydride and a catalyst are mixed, heated to 150° C. under nitrogen atmosphere protection, and reacted for 150 minutes; 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, itaconic acid and a polymerization inhibitor are added, the temperature is raised to 210° C., the system is reacted until the state is transparent, the vacuum degree is reduced, the negative pressure is stabilized at 0.07 MPa, vacuuming for 60 minutes, reacting until the acid value is less than 5 mgKOH / g, and cooling to room temperature to obtain a main resin; the main resin is prepared from the following mass components: 3 parts of trimethylolpropane, 18 parts of 2-butyl-2-ethyl-1,3-propanediol, 11 parts of neopentyl glycol, 14 parts of phthalic anhydride, 2 parts of itaconic acid, 0.5 parts of catalyst dibutyltin oxide, and 0.5 parts of polymerization inhibitor p-hydroxyanisole;

[0080] The other processes and steps are the same as those in Example 1 to obtain metallic ink and printed products thereof.

[0081] Comparative Example 4: A printing process of flexographic metal ink, comprising the following process steps:

[0082] In the dark, 62% polyester acrylic resin (Zhanxin resin) was added 416), 38% aluminum silver paste is mixed, pre-mixed by a gravity mixer, and ground by a grinder to a fineness of <5 μm to obtain a metallic ink;

[0083] Take metallic ink and use a 300L anilox roller for ink transfer printing at a printing speed of 80m / min; UV curing, UV curing irradiation speed of 80m / min, irradiation distance of 6cm, ultraviolet lamp 7000W, to form an ink layer.

[0084] Experiment: The metal inks obtained in Examples 1-3 and Comparative Examples 1-4 were printed on PET plastic films to obtain printed samples, and their properties were tested and the test results were recorded:

[0085] Gloss test: Use a gloss meter (60°) to test the gloss of the printed sample;

[0086] Adhesion test: Take GB / T 9286 as the reference standard, take the printed sample, make a grid on its surface, make 10 grids in both horizontal and vertical directions, stick 3M810 tape to the grid surface, scrape it with your fingers, let it stand for 15 seconds, and peel it off quickly at 135°50cm / s; judge the ASTM grade and record it;

[0087] Aging resistance test: Place the sample in an aging box, take it out after 44 hours, test the gloss of the sample, and calculate its light loss rate; Aging box environment: black standard temperature 64℃, test room temperature 45℃, irradiance 0.75W / m2, irradiation wavelength 420nm, relative humidity 70%;

[0088] Flexibility test: Curl the printed sample along a larger shaft rod to observe whether the ink layer is damaged; if no breakage occurs, continue to curl along a smaller shaft rod until the shaft rod where the ink layer breaks is encountered. The minimum shaft rod diameter that does not cause damage to the ink layer is used as the experimental indicator.

[0089] Glossiness(°) Adhesion grade Gloss loss rate (%) Flexibility(mm) Example 1 83 4B 6.6 1.0 Example 2 85 5B 6.1 2.0 Example 3 86 5B 6.4 1.0 Comparative Example 1 81 4B 6.8 2.0 Comparative Example 2 89 4B 8.3 4.0 Comparative Example 3 72 3B 10.5 4.0 Comparative Example 4 62 3B 14.4 2.0

[0090] According to the data in the above table, we can clearly draw the following conclusions:

[0091] The metal ink and printed products obtained in Examples 1-3 are compared with the metal ink and printed products obtained in Comparative Examples 1-4. The test results show that:

[0092] Compared with the comparative example, the printed products made of the metallic ink obtained in Examples 1-3 have higher glossiness, adhesion level and lower gloss loss rate and flexibility data, which fully demonstrates that the present invention achieves the improvement of the mechanical properties, aging resistance, adhesion ability and glossiness of the printed products made of the metallic ink.

[0093] Compared with Example 1, Comparative Example 1 does not set ester alcohol dodeca-methacrylate and ethylene glycol methyl ether methacrylate as active monomer components; the same as Example 1, Comparative Example 2 replaces the polyhydroxy rosin compound with rosin diacid; Comparative Example 3 replaces the polyhydroxy rosin compound with trimethylolpropane; the metallic ink and its printing process in Comparative Example 4 are changed. The gloss and adhesion grades of the metallic ink and its printed products obtained in Comparative Examples 1-4 are reduced, and the gloss loss rate and flexibility data are increased. It can be seen that the setting of the metallic ink and its printing process of the present invention can promote the improvement of the comprehensive properties of the printed products made of the metallic ink, such as mechanical properties, aging resistance, adhesion ability and gloss.

[0094] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0095] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A flexographic metal ink, characterized in that it comprises the following mass components: 32% to 36% of a main resin, 21% to 25% of an active monomer, 36% to 40% of an aluminum-silver paste, and 4% to 6% of an initiator; The main resin is prepared by the following process: The polyhydroxy rosin compound, phthalic anhydride and catalyst are mixed, heated to 150-160°C under nitrogen atmosphere protection, and reacted for 100-150 minutes; 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, itaconic acid and a polymerization inhibitor are added, the temperature is raised to 210-220°C, and reacted to obtain a main resin; The polyhydroxy rosin compound is prepared by the following process: 1.

1. Mix linoleic acid, pimaric acid and deionized water, add catalyst and activated clay, heat and melt under nitrogen atmosphere, raise the temperature to 230-250°C, control the pressure of the pressure reactor at 0.4-0.6MPa, react for 4-6h to obtain rosin diacid; 1.

2. Mix diglycidyl ether, rosin diacid and tetrabutylammonium bromide, raise the temperature to 130-140°C, and keep the temperature to react to obtain a dihydroxy rosin compound; A potassium hydroxide aqueous solution is added, and the temperature is raised to 80-90° C. to react for 10-12 hours to obtain a polyhydroxy rosin compound.

2. A flexographic metallic ink according to claim 1, characterized in that: The main resin is prepared from the following components by mass: 22 to 27 parts of polyhydroxy rosin compound, 18 to 22 parts of 2-butyl-2-ethyl-1,3-propanediol, 11 to 13 parts of neopentyl glycol, 14 to 20 parts of phthalic anhydride, 2 to 5 parts of itaconic acid, 0.1 to 1.0 parts of catalyst, and 0.1 to 1.0 parts of inhibitor.

3. The flexographic metallic ink according to claim 1, characterized in that: In step 1.1, rosin diacid is prepared from the following mass components: 2.0-2.2 parts of pimaric acid, 10 parts of linoleic acid, 0.10-0.15 parts of catalyst, and 1.0-1.5 parts of activated clay.

4. The flexographic metallic ink according to claim 1, characterized in that: In step 1.2, the diglycidyl ether is one of 1,6-hexanediol diglycidyl ether and 1,2-cyclohexanediol diglycidyl ether; The mass ratio of diglycidyl ether to rosin diacid is (1.2-1.4):

1.

5. The flexographic metallic ink according to claim 1, characterized in that: The active monomers include the following components by mass: 14 to 15 parts of methyl methacrylate, 23 to 25 parts of styrene, 11 to 13 parts of 2-hydroxyethyl methacrylate, 37 to 40 parts of butyl acrylate, 4 to 5 parts of n-butyl methacrylate, 3 to 15 parts of trimethylolpropane triacrylate, 1 to 8 parts of ester alcohol dodeca-methacrylate, and 3 to 5 parts of ethylene glycol methyl ether methacrylate.

6. A printing process of flexographic metallic ink according to any one of claims 1 to 5, characterized in that: The process comprises the following steps: taking the metal ink for ink transfer printing; then covering the surface of the metal ink with a release film, flattening it, UV curing it, and forming an ink layer; and finally peeling off the release film from the ink layer.

7. A printing process of flexographic metallic ink according to claim 6, characterized in that: The metal ink is prepared by the following process: under light-proof conditions, a main resin, an active monomer and an initiator are mixed, and aluminum-silver paste is added, premixed and ground.

8. A flexographic metallic ink printing process according to claim 7, characterized in that: The initiator is a compound of photoinitiators Irgacure-907 and Irgacure-1173, with a mass ratio of 1:1.

Citation Information

Patent Citations

  • Printing and leveling process of MEMS (Micro Electro Mechanical System) package carrier

    CN114103500A

  • Offset printing UV metal ink and preparation method thereof

    CN115093746A